Rapid identification and susceptibility pattern of various Candida isolates from different clinical specimens in a tertiary care hospital in Western Uttar Pradesh - Singh, Rajani; Verma, Rajesh K.; Kumari, Sunita; Singh, Amit; Singh, Dharmendra P. (International Journal of Research in Medical Sciences, 2017)
Background: Candida species are component of normal flora of human beings. Candidiasis is the commonest fungal disease affecting mucosa, skin, nails and internal organs. A variety of predisposing factors are known to cause candidiasis either by altering balance of normal microbial flora of the body or by lowering the host defence. Methods: A total of 90 specimens submitted in the department of microbiology were included in this study. Identification of Candida species as well as antifungal sensitivity testing was performed with Vitek®2 compact (Biomerieux France) using Vitek2 cards for identification of yeast and yeast like organisms (ID-YST cards). Antifungal susceptibility testing was performed using Vitek2 fungal susceptibility card (AST YS01) kits respectively. Results: The distribution of the clinical samples were urine 53 (58.9%), sputum 14 (15.5%), blood 10 (11.1%), nail 6 (6.7%) and high vaginal swab 7 (7.8%). Among 90 clinical isolates, species obtained were C. tropicalis 53 (59%), C. albicans 23 (25.5%), C. glabrata 6 (6.7%), C. parapsilosis 4 (4.4%), C. krusei 2 (2.2%), C. pelliculosa 1 (1.1%), C. famata 1 (1.1%). Conclusions: Infections caused by non-candida albicans species have increased. Identification of Candida species and their antifungal susceptibility are important for the treatment of hospitalized patients with serious underlying disease.